2015
DOI: 10.5958/0976-0571.2015.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abiotic and biotic factors on incidence of pests and predator in cowpea[Vigna unguiculata(L.) walp.]

Abstract: Field experiments were conducted during Kharif season of 2007-2008. The pest population was recorded in cowpea field aphids, jassid, thrips and pod borer and its highest population 116.20/15 cm shoots tip, 8.6/compound leaves, 5.87/flower bud and 0.73/flower bud and 1.8/pod, respectively. Abiotic factors like temperature, relative humidity, extent and distribution of rainfall, sunshine hour etc. influenced the infestation and stabilization of various insect pests in cowpea. The populations of aphids and pod bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 4 publications
6
11
1
Order By: Relevance
“…These finding are in conformity with Kumar et al, (2015) reported that Thrips (Megalurothripssjostedti Tryb.) population was observed in last week of September and its highest population was recorded in third week of October (5.87/flower bud).…”
Section: Seasonal Activity Of Cowpea Flower Thrips (M Sjoestdi Trybom)supporting
confidence: 81%
See 1 more Smart Citation
“…These finding are in conformity with Kumar et al, (2015) reported that Thrips (Megalurothripssjostedti Tryb.) population was observed in last week of September and its highest population was recorded in third week of October (5.87/flower bud).…”
Section: Seasonal Activity Of Cowpea Flower Thrips (M Sjoestdi Trybom)supporting
confidence: 81%
“…Weekly observations on major insect pest population available in the experimental field were recorded on randomly selected five plants from experimental plots during the whole cropping season i.e. from September 2015 to December 2015.The method modified as according to (Jackai, 1982;Kumar and Kumar, 2015). Correlation analysis was worked out as per method given by Gomez and Gomez (1984).…”
Section: Methodsmentioning
confidence: 99%
“…Pests under the strongest control pressure in the east are Bursaphelenchus xylophilus, Hyphantria cunea, and Mikania micrantha, while in the west, the most pressured pests are forest pikas [17,18]. As a result of the threat of global warming, and the pressure from economic development from southeast to northwest, transportation has carried along invasive pests that are spreading rapidly across regions with suitable environments and fewer natural enemies [19][20][21]. As this trend continues, even the unsuitable environment of the northwest now has more forest pests, while the lower capacity for the control of potential damage in the region places a heavier burden on local governments to take the necessary measures to control this potentially disastrous situation.…”
Section: Introductionmentioning
confidence: 99%
“…The government has already established a forest pest-control system via the State Forest Administration with a primary level consisting of forest quarantine or monitoring stations and other cooperative organizations for the prevention of pest outbreaks [44]. However, overall, the burden of control is carried out by the primary forest stations in the counties with weaker infrastructures, and the funds are mostly input by the local governments, triggering an extremely unjust imbalance in the control measures in each province, even when considering the "Hu line" distribution regularities [19][20][21]. In particular, after Premier Li Keqiang stated that China should break the traditional demographic pattern in order to allow people from all regions to benefit from modernization, the government put forward several policies, such as poverty reduction, ecological construction, and other supports to erase the imbalance barrier of the "Hu line" [45].…”
Section: Introductionmentioning
confidence: 99%
“…In Colombia, cowpea is produced by small farmers in the seven departments of the Atlantic coast, due to their adaptation to their climate and soil conditions, as in other tropical and subtropical areas of the world, but their yields are considered low (600 kg ha -1 ) compared to those in the United States and Peru, which yielded 1.790 and 1.376 kg ha -1 in 2014 (FAO, 2017). Low yields are attributed to the use of obsolete varieties and to susceptibility to biotic and abiotic factors, especially drought and high temperatures (Kumar and Kumar, 2015). For Ribeiro et al (2014), the genetic improvement by programs of public entities has allowed to increase the yields and the adaptation to different systems of production.…”
Section: Introductionmentioning
confidence: 99%